EVALUASI KESESUAIAN LAHAN PADI SAWAH (Oryza sativa L.) DI KABUPATEN LUWU - Anwar Robbo; Muliaty Galib (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Rice is one of the food crops and commercial crops. Rice also has the potential to contribute significantly to increasing income and employment in rural areas. As indicated by rice imports from Thailand and Vietnam, national rice production has not been able to meet domestic demand. The objectives of this study were (1) to determine the actual and potential land suitability levels of rice plants in Luwu Regency and (2) to find out the limiting factors for actual and potential land suitability of rice plants in Luwu Regency. Evaluation of rice land suitability using the FAO method. Based on the limiting factors of land characteristics. The results showed that the actual land suitability of plants was marginal (S3fn) with the limiting factors for nutrient retention (organic C) and available nutrients (P2O5 and K2O). Efforts to improve the limiting factor can be made by adding 59.6 t organic matter ha-1, 332.6 kg P2O5 ha-1, and 98 kg K2O ha-1 so that the actual land suitability of marginal (S3) becomes very suitable (S1).